Upplevelseproduktion som en lärandemetod : En litteraturstudie om hur upplevelseproduktion och pedagogik kan kombineras till ett nytt koncept för framtidens lärande - Ljungkrantz, Sara (2013)
This essay written on c-level is a final examination in experience production, a university program in Piteå at the Department of Arts, Communication and learning, which is a part of Luleå University of Technology (LTU).The introduction of the essay starts with a presentation of the topic, why it is of interest for the writer and a description of the program for experience production. Furthermore, presents the theories of experience production that is related to the essay and important theoretical parts of generations, teaching, learning and Human Dynamics, which is the basis for the work.The purpose of this essay is to combine theories of experience society and experience production with educational theories to develop a concept for future learning that is more personalized and consideration for students with special needs.In order to answer the research questions:• What theories of the experience society and experience production can be applied to personalized learning?• How can this be combined with educational theory and together strengthen a personalized future learning?. a literature review have been conducted and further a concept development.The study was conducted to show that there are similarities between the theories of experience production and pedagogical theories. A combination of these theories can ease the learning process in school. Even organizations or projects such as Framtidens lärande can develop by using new skills they not already possess about learning.Keywords: Experience production, experience community, experiential learning, future learning, individualized learning, pedagogy, learning disabilities Validerat; 20130619 (global_studentproject_submitter)